Effect of nanoclay on thermal, mechanical and liquid absorption properties of epoxy-clay nanocomposite - Quyen, Nguyen Cong; Yen Oanh, Doan Thi; Duy Linh, Nguyen Pham; Chuong, Bui (Vietnam Journal of Chemistry, 2016)
Composite materials based on epoxy DER 331 hot cured by MHHPA with several contents of nanoclay I28E were prepared and characterized by TEM and SEM. Results showed that the nanostructures were created in two levels: intercalated structure and nanoparticles (cluster). The interaction between nanoclay and epoxy matrix was evaluated by properties such as: liquid absorption, TGA and DMA. It was shown that nanostructures of cluster, as well as the hydrophobic behavior of material with the presence of nanoclay have dominant effect to liquid absorption. Otherwise, the thermal stability was affected mainly by intercalation structure. Results of DMA showed that the interaction of epoxy-clay was strongly destroyed at the temperature higher than material Tg. Keywords. Epoxy-nanoclay composites, liquid absorption, thermal property.